The analysis of ENR 50 rubber grafted with methyl methacrylate by means of chromatographic techniques - Graef, Sven Markus (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.) -- University of Stellenbosch, 1999.